PENGARUH PENERAPAN MEDIA E-BOOK INTERAKTIF BERBASIS CANVA TERHADAP KECERDASAN EMOSIONAL WARGA BELAJAR DI LEMBAGA PELATIHAN MORALITAS BUDI PEKERTI BANGSA INDONESIA - Jelita Tessalonika; Fauzi Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low levels of emotional intelligence among learners at the Indonesian Nation's Character Moral Training Foundation, which stems from abstract, one-way moral learning methods that fail to foster emotional regulation. The purposes of this study are to describe the implementation of Canva-based interactive e-book media, determine learners' emotional intelligence levels, and ascertain the extent of the interactive e-book's influence as an instructional stimulant on learners' emotional intelligence. This study is a quantitative research employing a quasi-experimental approach with a One-Group Time Series Design model. The study involved all 35 learners at the foundation as a total sampling size. Data were collected through a questionnaire based on the Situational Judgment Test (SJT), which demonstrated high reliability (α= 0.842), and complemented by daily behavior observation sheets. Data analysis techniques included descriptive analysis, tendency testing, simple linear regression analysis, and the Paired Sample T-Test. The results indicated that the Canva-based interactive e-book was systematically implemented through preparation, implementation, and evaluation stages via a guided screen-sharing method. Furthermore, statistical analysis confirmed that the implementation of the Canva-based interactive e-book provided a significant contribution, accounting for a 66.4% variance in the improvement of learners' emotional intelligence (Fcount = 68.45, p = 0.000 < 0.05). The Paired Sample T-Test further verified that Ha is accepted (p= 0.000). In conclusion, the implementation of Canva-based interactive e-book media exerts a significant and positive influence on enhancing the emotional intelligence of learners.